مقارنة بين صندوق التروس العادي والاوتوماتيك - مؤيد محمد عوض يوسف; أحمد محمد الحسن الطيب (جامعة الشيخ عبدالله البدري, 2023)
يتلخص البحث في التعرف علي صندوق السرعات ووظيفته ومهامه وتحديد انواعه، وتوضيح اجزاء كل من صندوق التروس اليدوي واالوتوماتيك والحديث عن مبدأ عمل صندوق التروس اليدوي واالوتوماتيك وذكر مميزات كل من النوعين ، وشرح مفصل لألعطال ومسبباتها وكيفية اصالحها ، واستخالص اوجه المقارنة بين صندوق التروس اليدوي واالتوماتيك للحصول علي نتائج مفيدة Abstract The Research is Summarized in identifying the gearbox, its function, its tasks, identifying its types, clarifying the parts of both the manual and automatic gearbox, taking about the principle of the manual and automatic gearbox work, mentioning the characteristics of each of the faults and their causes, how to fix them, and drawing comparison between the manual and automatic gearbox to obtain results useful.